Hybrid Warfare in the Digital Age: Cyberpower, AI, and the Future of Global Security - Muhammad Sanaullah Khan; Farhat Asghar Rana; Zoha irfan (`, 2025)
This paper discusses how cyber capabilities and Artificial Intelligence (AI) have changed the nature and conduct of hybrid warfare and how they have produced a more deadly paradigm of Algorithmic Hybrid Warfare. By using a qualitative analysis of recent conflict and the use of cyber operations, specifically Russian action in Ukraine, Chinese, and Iranian state-sponsored campaigns, the study shows that cyber operations have changed, no longer a secondary tactic; instead, it has become one of the main pillars of hybrid strategy, and it can be used to conduct pre-positioning, disruption, and long-term coercion. Moreover, the combination of AI has become a force multiplier by automating cyber-attacks using adaptive malware, transforming information warfare by using AI-generated disinformation, and optimizing kinetic attacks through intelligent target detection. The results indicate that this synergy generates an asymmetric threat environment in which the speed, scale and strategic ambiguity are unprecedented and that significantly augments the problems of attribution and disables traditional deterrence strategies premised on retaliation. The article finds that current national security arrangements, international legal regimes, and alliances- all developed to deal with an earlier age of conventional warfare- are grossly inadequate to address this dynamic threat. It concludes that responding to this vulnerability requires a paradigm shift to whole-of-society resilience, collective defense modernization and the urgent development of new international norms of responsible state behavior in cyberspace and AI governance. Keywords: Hybrid Warfare, Cybersecurity, Artificial Intelligence, Disinformation, Global Security, Deterrence, Autonomous Systems